Improvement in SRS-22R Self-Image Correlate Most with Patient Satisfaction after 3-Column Osteotomy. Issue 12 (15th June 2021) - Gum, Jeffrey L.; Shasti, Mark; Yeramaneni, Samrat; Carreon, Leah Y.; Hostin, Richard A.; Kelly, Michael P.; Lafage, Virginie; Smith, Justin S.; Passias, Peter G.; Kebaish, Khaled; Shaffrey, Christopher I.; Burton, Douglas L.; et al.
Abstract : Study Design: Longitudinal cohort. Objectives: The aim of this study was to examine the relationship between patient satisfaction, patient-reported outcome measures (PROMs) and radiographic parameters in adult spine deformity (ASD) patients undergoing three-column osteotomies (3CO). Summary of Background Data: Identifying factors that influence patient satisfaction in ASD is important. Evidence suggests Scoliosis Research Society-22R (SRS-22R) Self-Image domain correlates with patient satisfaction in patients with ASD. Methods: This is a retrospective review of ASD patients enrolled in a prospective, multicenter database undergoing a 3CO with complete SRS-22R pre-op and minimum 2-years postop. Spearman correlations were used to evaluate associations between the 2-year SRS Satisfaction score and changes in SRS-22R domain scores, Oswestry Disability Index (ODI), and radiographic parameters. Results: Of 135 patients eligible for 2-year follow-up, 98 patients (73%) had complete pre- and 2-year postop data. The cohort was mostly female (69%) with mean BMI of 29.7 kg/m 2 and age of 61.0 years. Mean levels fused was 12.9 with estimated blood loss of 2695 cc and OR time of 407 minutes; 27% were revision surgeries. There was a statistically significant improvement between pre- and 2-year post-op PROMs and all radiographic parameters except Coronal Vertical Axis. The majority of patients had an SRS Satisfaction score of ≥3.0 (90%) or ≥4.0 (68%), consistent with a moderate ceiling effect. Correlations of patient satisfaction was significant for Pain (0.43, P < 0.001), Activity (0.39, P < 0.001), Mental (0.38, P = 0.001) Self-Image (0.52, P < 0.001). ODI and Short-Form-36 Physical component summary had a moderate correlation as well, with mental component summary being weak. There was no statistically significant correlation between any radiographic or operative parameters and patient satisfaction. Conclusion: There was statistically significant improvement in all PROMs and radiographic parameters, except coronal vertical axis at 2 years in ASD patients undergoing 3CO. Improvement in SRS Self-Image domain has the strongest correlation with patient satisfaction. Level of Evidence: 3 Abstract : In 99 patients undergoing three-column osteotomy for adult spinal deformity, there was significant improvement in all Scoliosis Research Society-22R domain scores. Self-Image had the strongest association with patient Satisfaction 2 years after surgery, followed by Pain and Activity. There were no associations between any radiographic or operative parameters and patient satisfaction.